Big data : video edition - Marz, Nathan; Warren, James (James O.), 1974- (Manning Publications, 2015)
"Big Data teaches you to build big data systems using an architecture that takes advantage of clustered hardware along with new tools designed specifically to capture and analyze web-scale data. It describes a scalable, easy-to-understand approach to big data systems that can be built and run by a small team. Following a realistic example, this Video Editions book guides readers through the theory of big data systems, how to implement them in practice, and how to deploy and operate them once they're built."--Resource description page